Physical Characteristics and Performance Tests in Male Water Polo: A Multiple Regression Analysis on Youth - Melchiorri, Giovanni; Triossi, Tamara; Bianchi, Daniele; Tancredi, Virginia; Viero, Valerio (International journal of environmental research and public health, 2022)
Background: In water polo, more physical and performance variables are related to a performance in a match. The aim of our work was therefore: (a) to evaluate the relationships between anthropometric characteristics and performance tests and performance in a match in young male water polo players; (b) to propose new guidelines for match analysis. Methods: Multiple regression analysis was used to study the results in anthropometric evaluations (height, body mass, chest circumference, arm span, non-dominant arm length) and performance tests (push-up, chin-up, shuttle swim test, sprint swim 10 m, eggbeater kick, 100 m swimming) and two coaches’ evaluations of two friendly matches using new guidelines. A total of 130 subjects (age: 15.6 ± 0.9 years) were involved in the study. Results: In this study, we proposed a new performance model based on multiple regression analysis (r = 0.85, r2 = 0.73, adjusted r2 = 0.57) and described by the following equation: Coach’s Evaluation = 151.6 + (−0.016 × height) + (0.6 × body mass) + (−0.82 × chest) + (−0.59 × arm span) + (0.75 × non dominant arm length) + (−0.037 × push up) + (0.17 × chin up) + (5.87 × shuttle swim test) + (−2.2 × 10 m sprint swim) + (0.05 × eggbeater kick) + (−0.35 × 100 m swimming). Inter-observer values were: CV: −3.9%, ICC: 0.82, ES: 0.1. Intra-observer: CV: −4.1%, ICC: 0.96, ES: 0.06. Conclusions: The relationships between anthropometric and performance variables and the match analysis have been statistically described. The equation found can be used to predict the overall performance of a player and permits evaluations of how much the improvement in one of the qualities can affect the players’ overall performance. Moreover, the new method for match analysis we have proposed showed a good reliability and can be used for new studies on water polo.